Impact of divertor material on neutral recycling and discharge fueling in DIII-D. (13th March 2020) - Bykov, I; Rudakov, D L; Pigarov, A Yu; Hollmann, E M; Guterl, J; Boedo, J A; Chrobak, C P; Abrams, T; Guo, H Y; Lasnier, C J; McLean, A G; Wang, H Q; et al.
Abstract: Experiments with the lower divertor of DIII-D during the Metal Rings Campaign (MRC) show that the fraction F of atomic D in the total recycling flux is material-dependent and varies through the ELM cycle, which may affect divertor fueling. Between ELMs, F C  ∼ 10% and F W  ∼ 40%, consistent with expectations if all atomic recycling is due to reflections. During ELMs, FC increases to 50% and F W to 60%. In contrast, the total D recycling coefficient including atoms and molecules R stays close to unity near the strike point where the surface is saturated with D. During ELMs, R can deviate from unity, increasing during high energy ELM-ion deposition (net D release) and decreasing at the end of the ELM which leads to ability of the target to trap the ELM-deposited D. The increase of R  > 1 in response to an increase in ion impact energy E i has been studied with small divertor target samples using Divertor Materials Evaluation System (DiMES). An electrostatic bias was applied to DiMES to change E i by 90 eV. On all studied materials including C, Mo, uncoated and W-coated TZM (>99% Mo, Ti, and Zr alloy), W, and W fuzz, an increase of E i transiently increased the D yield (and R ) by ∼10%. On C there was also an increase in the molecular D2 yield, probably due to ion-induced D2 desorption. Despite the measured increase in F on W compared to C, attached H-mode shots with OSP on W during MRC did not demonstrate a higher pedestal density. About 8% increase in the edge density could be seen only in attached L-mode scenarios. The difference can be explained by higher D trapping in the divertor and lower divertor fueling efficiency in H- versus L-mode.